2022
DOI: 10.1002/stc.3137
|View full text |Cite
|
Sign up to set email alerts
|

Modal identification and damping performance of a full‐scale GFRP‐SFRSCC hybrid footbridge

Abstract: Slender footbridges are prone to excessive vibrations due to pedestrian effects, and comfort criteria often govern their design. In this sense, composite materials that combine high damping capacity with relatively high stiffness and low mass can provide functional benefits. This paper presents a study of the dynamic behaviour of an 11 m long hybrid footbridge made of two I-shaped pultruded glass fibre reinforced polymer (GFRP) main girders and a thin steel fibre reinforced self-compacting concrete (SFRSCC) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…With the rapid development of sensor technology, the complex responses and characteristics of certain bridge structures can be acquired. Building upon this foundation, an increasing number of bridges have been assessed in research on monitoring, early warning, and operational status based on data information [26,27].…”
Section: Principles Of Bearing Reaction Monitoring and Early Warning ...mentioning
confidence: 99%
“…With the rapid development of sensor technology, the complex responses and characteristics of certain bridge structures can be acquired. Building upon this foundation, an increasing number of bridges have been assessed in research on monitoring, early warning, and operational status based on data information [26,27].…”
Section: Principles Of Bearing Reaction Monitoring and Early Warning ...mentioning
confidence: 99%
“…The characteristics of structures (e.g., modal parameters [7,8]) are influenced by the natural environment (wind, temperature, etc.). Wind is one of the critical loads for longspan cable-stayed bridges and can cause vortex-induced vibrations of decks and cables and rain-wind-induced vibrations of cables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human-structure interaction [28][29][30][31][32][33][34][35][36][37] plays an important role in these lightweight bridges, as several studies in the past have already shown. Indeed, the modal parameters, such as the first natural flexural frequency and the structural damping ratio, are significantly influenced [38][39][40][41][42][43][44][45] by it. Due to the interaction, the pedestrians, who both generate the vibration while walking and/or jogging on the bridge deck, as well as dampen this induced vibration by means of the ligaments in the human body [46], will strongly influence the comfort on the lightweight footbridges.…”
Section: Introductionmentioning
confidence: 99%